Relapse of porphyria cutanea tarda after treatment. (1st December 2018) - Salameh, H.; Sarairah, H.; Rizwan, M.; Kuo, Y.‐F.; Anderson, K.E.; Singal, A.K.
Summary: Porphyria cutanea tarda (PCT) is a skin disease causing a rash and sunlight sensitivity. Patients affected by this condition can be treated by removing some of their blood, or with a medication that is also used to prevent and treat malaria (antimalarials). In this study, the authors compared the effectiveness of these quite different treatment approaches. They included data on patients, from previous clinical studies, who were treated for PCT and monitored for at least one year after their symptoms had cleared. They aimed to assess PCT disease recurrence (i.e. the symptoms returning) either by skin rash, sunlight sensitivity or an elevation in a certain blood test. Authors included data on patients from 5 clinical studies in which patients received high dose of antimalarial medication, 5 clinical studies in which patients received low dose antimalarial medication and 3 clinical studies in which patients were treated by removing some of their blood. While one third of the patients treated with either high or low dose antimalarial medication experienced disease recurrence, only one fifth of patients treated by removing blood experienced such disease recurrence. Their study showed that if 100 patients were followed for one year, disease recurrence will happen in 8 patients receiving high dose antimalarials, 17 patients receiving low dose antimalarials, and 5 patients undergoing blood removal. The authors concluded that the recurrence is lowest if the PCT is treated by blood removal. However, larger studies are needed to better define recurrence rate of PCT after treatment with one of the two treatments.